41 Increase in uterine serous carcinoma: will it surpass uterine endometrioid cancer? A population analysis of 720, 984 uterine cancer patients. (13th November 2020) - Liao, C; Tran, K; Richardson, M; Darcy, K; Tiao, C; Hamilton, CA; Maxwell, L; Mann, A; Cohen, J; Kapp, DS; Chan, J
Abstract : Objective: To evaluate the trends of uterine serous carcinoma compared to endometrioid uterine cancer. Methods: From 2001–2016, incidence rates were estimated from United States Cancer Statistics after correcting for hysterectomy prevalence based on Behavioral Risk Factor Surveillance System data. SEER*Stat and Joinpoint regression were used to calculate incidence (per 100, 000) and average annual percent change (AAPC). Results: Of 720, 984 patients (78% White, 10% Black, 8% Hispanic, 3% Asian/Pacific-Islander), the proportion of endometrioid, uterine serous carcinoma (USC), clear-cell, and sarcoma were 73.7%, 5.9%, 1.3%, and 2.0% respectively. In 2016, incidence of endometrioid was approximately 10-fold higher than USC (30.6 vs. 3.6). Of USC patients, the age group with the highest incidence was 75–79 year olds (24.7). Of note, Blacks had the highest incidence of USC at 9.1 compared to 3.0 in Whites. Over the 15 year study period, there was a 4.6% increase in USC per year compared to no increase in endometrioid cancer (p<0.05). Of USC patients, the highest increase was in ages 70–74 (AAPC 5.7%). Blacks, Hispanics, and Whites had an annual increase of +6.7%, +8.6%, and +4.3%, respectively. The intersectionality of age 70–74 and Black with USC had an AAPC of +7.3%. A predictive model shows USC incidence would surpass endometrioid in Blacks within 15 years. Conclusion: Compared to Whites, Blacks have a 3-fold higher overall incidence of uterine serous cancer and is increasing at 6.7% per year. For Black women, this aggressive histology is projected to surpass endometrioid cancer in 15 years.